Noninvasive Ventilation in the Critically Ill Patient With Obesity Hypoventilation Syndrome: A Review. - Sequeira, T (2017)
Obesity is a global epidemic that adversely affects respiratory physiology. Sleep-disordered breathing and obesity hypoventilation syndrome (OHS) are among the most common pulmonary complications related to obesity class III. Patients with OHS may present with acute hypercapnic respiratory failure (AHRF) that necessitates immediate noninvasive ventilation (NIV) or invasive ventilation and intensive care unit (ICU) monitoring. The OHS is underrecognized as a cause of AHRF. The management of mechanical ventilation in obese ICU patients is one of the most challenging problems facing respirologists, intensivists, and anesthesiologists. The treatment of AHRF in patients with OHS should aim to improve alveolar ventilation with better alveolar gas exchange, as well as maintaining a patent upper airway, which is ideally achieved through NIV. Treatment with NIV is associated with improvement in blood gases and lung mechanics and may reduce hospital admissions and morbidity. In this review, we will address 3 main issues: (1) NIV of critically ill patients with acute respiratory failure and OHS; (2) the indications for postoperative application of NIV in patients with OHS; and (3) the impact of OHS on weaning and postextubation respiratory failure. Additionally, the authors propose an algorithm for the management of obese patients with AHRF.